Pembangunan Video Animasi 3 Dimensi Tentang Bahaya Narkoba, HIV Aids Dan Seks Bebas - Hakim, Frestika Cahyo; Wardati, Indah Ully (APMMI - Asosiasi Profesi Multimedia Indonesia, 2013)
ABSTRACT Currently drug problems, HIV / AIDS and promiscuity often discussed. Many cases that occur due to drugs, HIV / AIDS and free sex. With the drug problems, HIV / AIDS and free sex happens in Pacitan, many speakers giving advice on the dangers of drugs, HIV / AIDS and free sex in order to later drug problems, HIV / AIDS and free sex did not increase much. Then be made to the media information in the form of 3-D animated video about the dangers of drugs, HIV / AIDS and free sex. The purpose of this research is the creation of three-dimensional animated video about the dangers of drugs, HIV / AIDS and free sex that does not fall into that issue and assist communicators in providing materials about the dangers of drugs, HIV / AIDS and promiscuity. The benefit of this study is as a medium of information about the dangers of drugs, HIV / AIDS and free sex. Teens can avoid drugs, HIV / AIDS and free sex and can choose a healthy society, free from drugs, HIV / AIDS and free sex.Methods band is used in the manufacture of 3-D video animation writer uses library methods, observation and interviews. Designing using 3Ds Max 2010, Sony Vegas Pro 10, Adobe Photoshop CS3 and Corel Draw X4. Keywords: Drugs, HIV AIDS and Free Sex ABSTRAKSI Saat ini masalah narkoba, HIV / AIDS dan seks bebas sering sekali dibicarakan. Banyak kasus yang terjadi akibat narkoba, HIV / AIDS dan seks bebas. Dengan adanya masalah narkoba, HIV / AIDS dan seks bebas yang terjadi di Pacitan, banyak narasumber memberi nasehat tentang bahaya narkoba, HIV / AIDS dan seks bebas agar nantinya masalah narkoba, HIV / AIDS dan seks bebas tidak bertambah banyak. Maka dibuatlah media informasi berupa video animasi 3 dimensi tentang bahaya narkoba, HIV / AIDS dan seks bebas. Tujuan penelitian ini adalah terciptanya video animasi 3 dimensi tentang bahaya narkoba, HIV / AIDS dan seks bebas agar remaja tidak terjerumus dalam masalah itu dan membantu para komunikator dalam memberikan materi tentang bahaya narkoba, HIV / AIDS dan seks bebas. Manfaat dari penelitian ini adalah sebagai media informasi tentang bahaya narkoba, HIV / AIDS dan seks bebas. Remaja bisa menghindari narkoba, HIV / AIDS dan seks bebas serta bisa memilih pergaulan yang sehat, bebas dari narkoba, HIV / AIDS dan seks bebas. Metode yang di gunakan dalam pembuatan video animasi 3 dimensi penulis menggunakan metode pustaka, observasi dan wawancara. Perancangan menggunakan 3Ds Max 2010, Sony Vegas Pro 10, Adobe Photoshop cs3 dan Corel Draw X4. Kata Kunci : Narkoba, HIV AIDS dan Seks Bebas